Linguistic manipulation of the victim’s media image. A portrait of Sharon Tate based on selected press coverage of the Tate-LaBianca murder case (Zjawiska propagandy i manipulacji w prasie, telewizji, radiu i Internecie, 2022)
The article aims to present how the American newspapers manipulated the media image of Sharon Tate and what consequences of that can be observed today. The first part focuses on concepts of manipulation and linguistic manipulation. Author introduces perceptions of criminality, criminal offenders, and their victims in media, following by the outline of the circumstances of the Tate-LaBianca murders. Finally, the article presents the analysis of Sharon Tate's media image in selected press releases in the context of linguistic manipulation techniques.